PROSES PERUMUSAN KEBIJAKAN (Studi Kasus pada Program Jemput Sehat Warga Kota Bengkulu) - , YENNI FITHRIANI ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study discussed about the policy making process of Program Jemput Sehat Warga. It is one of populist policies that give attention to Promotive and Preventive health efforts and it has been one of superior program of the chosen mayor. At implementation, this program gets some resistances from street level bureaucrats. This research has a purpose to explain resistances that come up from policy making process perspective, including some actors involve in this process and their interests also. This research applied qualitative methods with descriptive approach. Data was collected by interview and documentation. Then, data was analyzed through three steps: data reduction, data presentation and decision making/verification. This research based on theory of policy process/political process with stagist approaches, pluralist-elitis approaches and policy discourse approaches. The research uses actor variable (values and interests) and policy making variable (agenda setting, formulation and legitimation). The study found that Program Jemput Sehat Warga of resistance at the implementation because there was no identification of agenda setting and problem definition is done by consensus of all stakeholders in the formulation of policy. The policy is elitist, because only the mayor and heads of agencies as an agenda setter. At the formulation also there is no role of street-level bureaucrats, whereas they will interact with the community to provide services specified in the policy. Interests of street level bureaucrats minimizing the risk and inconvenience in the work, maximizing revenues and personal satisfaction is not fully accommodated in the policy. Based on the study to minimize the resistance at the stage of policy implementation is recommended. (1) the formulation of policies removed from the local problems were found with the participation of the public, street-level bureaucrats (field officers), and other stakeholders in order to produce a comprehensive policy to solve problems that really exist in the community, (2) All policy stakeholders should consider all interests included in the draft policy.